ANALISIS HUBUNGAN TINGKAT PENDIDIKAN DENGAN PERILAKU KONSUMSI RUMAH TANGGA MASYARAKAT SUMATERA UTARA - Devi Fitriya Ningsih; Karmila Tanjung; Dini Lestari (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to examine the analysis of the relationship between educational level and Indonesian household consumption behavior. As in general, the first education of a child passing through the family. And the standard of living is said to be peaceful if the family meets the requirements meet the needs of both physical and spiritual life. Like consumer spending, We also have to pay attention to the costs incurred. Then, the child's education level seen in consumption. The sample of this research is the people of North Sumatra with database in 2021. In this study, the research method used in this study used literature search system.